Caspase Inhibition Protects against Reovirus-Induced Myocardial Injury In Vitro and In Vivo - DeBiasi, Roberta L. (American Society for Microbiology, 2004)
Viral myocarditis is a disease with a high morbidity and mortality. The pathogenesis of this disease remains poorly characterized, with components of both direct virus-mediated and secondary inflammatory and immune responses contributing to disease. Apoptosis has increasingly been viewed as an important mechanism of myocardial injury in noninfectious models of cardiac disease, including ischemia and failure. Using a reovirus murine model of viral myocarditis, we characterized and targeted apoptosis as a key mechanism of virus-associated myocardial injury in vitro and in vivo. We demonstrated caspase-3 activation, in conjunction with terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling and annexin binding, in cardiac myocytes after myocarditic viral infection in vitro. We also demonstrated a tight temporal and geographical correlation between caspase-3 activation, histologic injury, and viral load in cardiac tissue after myocarditic viral infection in vivo. Two pharmacologic agents that broadly inhibit caspase activity, Q-VD-OPH and Z-VAD(OMe)-FMK, effectively inhibited virus-induced cellular death in vitro. The inhibition of caspase activity in vivo by the use of pharmacologic agents as well as genetic manipulation reduced virus-induced myocardial injury by 40 to 60% and dramatically improved survival in infected caspase-3-deficient animals. This study indicates that apoptosis plays a critical role in mediating cardiac injury in the setting of viral myocarditis and is the first demonstration that caspase inhibition may serve as a novel therapeutic strategy for this devastating disease.